2005
DOI: 10.1521/pedi.19.1.84.62182
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders in Patients with Burning Mouth Syndrome

Abstract: Burning Mouth Syndrome (BMS) presents high rates of comorbid Axis I disorders while no controlled studies have addressed the question of Axis II comorbidities. The aim of the present study was to examine DSM-IV (APA, 1994) Axis II comorbidity in BMS patients and to control for the specificity of this association. Seventy BMS patients were compared to a nonpsychiatric population sample and to patients with other Somatoform Disorders for the presence of personality disorders (assessed with the Structured Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…Specific personality traits have previously been described for BMS patients, including anxiety, sad thoughts, concerns about health, and cancerophobia (11,17). IBMS patients feel more anxious and depressed than healthy controls (7,9,10,29-31) and have a greater prevalence of personality disorders than healthy subjects (32).…”
Section: Psychological Statusmentioning
confidence: 93%
“…Specific personality traits have previously been described for BMS patients, including anxiety, sad thoughts, concerns about health, and cancerophobia (11,17). IBMS patients feel more anxious and depressed than healthy controls (7,9,10,29-31) and have a greater prevalence of personality disorders than healthy subjects (32).…”
Section: Psychological Statusmentioning
confidence: 93%
“…Scores ranging from 0 to 7 suggest no or minimal symptoms of anxiety, whereas scores of 8 and above indicate the presence of anxiety. Previous research documented high reliability and diagnostic concordance for the Italian version of this scale [48, 49]. Ham-D and Ham-A were chosen because they are two widely used and accepted outcome measures for the evaluation of clinical features of anxiety and depression.…”
Section: Methodsmentioning
confidence: 99%
“…5 Some researchers have suggested that the disorder could be a manifestation of somatization, whereas others have reported that it is more closely related to neuropathic pain. [11][12][13][14][15][16][17][18][19][20][21] Some studies, but not all, have shown that depression and anxiety are associated with the variability of the pain suffered. 8 Most studies of BMS have shown a high frequency of psychiatric morbidity (somatization, obsessioncompulsion, cancerophobia, personal sensitivity, psychoticism, hostility and social isolation).…”
Section: Introductionmentioning
confidence: 99%